CHANGES IN BODY MASS, DRUG USE AND AGGRESSIVE BEHAVIOUR IN FORENSIC PATIENTS DURING THE COVID-19 PANDEMIC - Goran Arbanas; Marija Horina; Ante Periša; Nadica Buzina (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2022)
The main objective of this study was to assess behavioural changes in forensic patients (those assessed as not guilty by reason of insanity and sent for an involuntary forensic treatment) during the COVID-19 pandemic restrictions. There were 82 patients treated at the Department for Forensic Psychiatry of the University Psychiatric Hospital Vrapče in 2020, 45 of which stayed in the department for the whole year. Data were extracted from their charts and from the nurses’ reports about their body masses, additional therapy prescribed and incidents at the ward. During the lock-down due to the COVID-19 pandemic, the body masses of the forensic patients decreased signifi cantly in the first weeks of the lock-down and stayed low during the rest of 2020. Patients used fewer additional antipsychotics, benzodiazepines, hypnotics and pain killers in April 2020 as compared to February 2020. In June 2020, the use of these drugs returned to pre-pandemic levels, with the exception of antipsychotics. In August 2020, painkiller use increased to higher than pre-pandemic levels. The number of incidents during lock-down was lower compared to pre-pandemic levels.